Half-Life of Biodegradable Plastics in the Marine Environment Depends on Material, Habitat, and Climate Zone - Lott, Christian; Eich, Andreas; Makarow, Dorothée; Unger, Boris; van Eekert, Miriam; Schuman, Els; Reinach, Marco Segre; Lasut, Markus T.; Weber, Miriam (Frontiers in Marine Science, 2021)
The performance of the biodegradable plastic materials polyhydroxybutyrate (PHB), polybutylene sebacate (PBSe) and polybutylene sebacate co-terephthalate (PBSeT), and of polyethylene (LDPE) was assessed under marine environmental conditions in a three-tier approach. Biodegradation lab tests (20°C) were complemented by mesocosm tests (20°C) with natural sand and seawater and by field tests in the warm-temperate Mediterranean Sea (12–30°C) and in tropical Southeast Asia (29°C) in three typical coastal scenarios. Plastic film samples were exposed in the eulittoral beach, the pelagic open water and the benthic seafloor and their disintegration monitored over time. We used statistical modeling to predict the half-life for each of the materials under the different environmental conditions to render the experimental results numerically comparable across all experimental conditions applied. The biodegradation performance of the materials differed by orders of magnitude depending on climate, habitat and material and revealed the impreciseness to generically term a material “marine biodegradable.” The half-life t0.5 of a film of PHB with 85 μm thickness ranged from 54 days on the seafloor in SE Asia to 1,247 days in mesocosm pelagic tests. t0.5 for PBSe (25 μm) ranged from 99 days in benthic SE Asia to 2,614 days in mesocosm benthic tests, and for PBSeT t0.5 ranged from 147 days in the mesocosm eulittoral to 797 days in Mediterranean benthic field tests. For LDPE no biodegradation could be observed. These data can now be used to estimate the persistence of plastic objects should they end up in the marine environments considered here and will help to inform the life cycle (impact) assessment of plastics in the open environment.